(untitled) (Tạp chí Y học Cộng đồng, 2025)
Objective: To determine key technical parameters of a competitive immunoassay dipstick for the rapid detection of Aflatoxin B1 (AFB1). Methods: Optimization was carried out for several parameters, including the concentration of coating antigen on the test line, storage conditions of the antibody–gold nanoparticle conjugate, the composition of the running buffer, and the volumes of reagents applied during testing. Results: The developed test strip demonstrated a detection limit of 0.01 µg/mL, with no cross-reactivity observed against standard samples of Aflatoxin M1, Ochratoxin A, and Patulin at tested concentrations. The test exhibited a sensitivity of 87.5% and a specificity of 95%. Conclusion: A competitive immunoassay dipstick test for the rapid detection of AFB1 was successfully developed by optimizing the antibody–gold conjugation process, the running buffer composition, and strip configuration. The test shows strong potential for on-site AFB1 screening in food safety monitoring.